Evaluation of zeolite content in volcanic tuff in the coastal chain (Latakia University Journal -Basic Sciences Series, 2023)
The research aims to evaluate the zeolite content of the samples of the study area, depending on the properties of ion exchange and X-ray analysis. The exchange capacity (CEC) of 9 samples from the crude deposits (JNM, BS9-10, MK-B, JS, BA, KH, A.D.B R, KSa,) was studied.This is done by altering its outer surface to the sodium form first and then replacing the sodium cations with ammonium ions. The sodium cation concentration in the final solution was measured using a flame spectrometer. The results showed that the exchange capacity of the samples ranged between 0.4-0.2 mmol/g.  X-Ray.D analysis of four samples showed that all samples contained one or more zeolite phases of analcime and phyllipsite type, noting the presence of two phases (dachiardite. jamesonden) distinguishing the study area from other regions in the country.